Pengaruh pemberian pupuk SP-36 dan pupuk kandang kelinci terhadap pertumguhan dan hasil tanaman kailan (Brassica oleraceae var achepala) - Apriana Nahak; Made Suarta; Ni Luh Komang Sulasmini Mudra (Fakultas Pertanian, Universitas Warmadewa, 2018)
The purpose of this study was to determine the effect of giving SP-36 fertilizer and rabbit manure as well as their interaction with the growth and yield of kailan plants. The study was conducted at the Garden Experiment Station, Faculty of Agriculture, Warmadewa University. This study took place from April 17 to June 5, 2018. The experiment was arranged factorially with two treatment factors and repeated three times in a Randomized Block Design (RBD). The first factor is SP-36 fertilizer with four dose levels namely P0= 0 kg ha-1 (without fertilizer), P1= 100 kg ha-1, P2= 200 kg ha-1, P3= 300 kg ha-1. The second factor is rabbit manure with four dose levels, namely K0= 0 ton ha-1 (without fertilizer), K1= 10 tons ha-1, K2= 20 tons ha-1, K3 = 30 tons ha-1. The results showed that giving rabbit manure up to 20 tons ha-1 increased the yield of kailan plants, which was 96.36 g, while the interaction and SP-36 fertilizer had no real effect.